Uncoupling antisense-mediated silencing and DNA methylation in the imprinted Gnas cluster. - Christine M Williamson (Public Library of Science (PLoS), 2011)
There is increasing evidence that non-coding macroRNAs are major elements for silencing imprinted genes, but their mechanism of action is poorly understood. Within the imprinted Gnas cluster on mouse chromosome 2, Nespas is a paternally expressed macroRNA that arises from an imprinting control region and runs antisense to Nesp, a paternally repressed protein coding transcript. Here we report a knock-in mouse allele that behaves as a Nespas hypomorph. The hypomorph mediates down-regulation of Nesp in cis through chromatin modification at the Nesp promoter but in the absence of somatic DNA methylation. Notably there is reduced demethylation of H3K4me3, sufficient for down-regulation of Nesp, but insufficient for DNA methylation; in addition, there is depletion of the H3K36me3 mark permissive for DNA methylation. We propose an order of events for the regulation of a somatic imprint on the wild-type allele whereby Nespas modulates demethylation of H3K4me3 resulting in repression of Nesp followed by DNA methylation. This study demonstrates that a non-coding antisense transcript or its transcription is associated with silencing an overlapping protein-coding gene by a mechanism independent of DNA methylation. These results have broad implications for understanding the hierarchy of events in epigenetic silencing by macroRNAs.